2014
DOI: 10.1097/qai.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Cotrimoxazole in Pregnancy

Abstract: Introduction Cotrimoxazole is widely prescribed to treat a range of infections and for HIV-infected individuals it is administered as prophylaxis to protect against opportunistic infections. Some reports suggest that fetuses exposed to cotrimoxazole during early pregnancy may have an increased risk of congenital anomalies. We carried out this systematic review in order to update the evidence of cotrimoxazole safety in pregnancy. Methods Three databases and one conference abstract site were searched in duplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 38 publications
(70 reference statements)
0
17
0
1
Order By: Relevance
“…The recent guidelines of the German Society of Gynecology and Obstetrics indicate that the treatment of VVC with the antimycotic agents available on the market is successful in most cases, and that polyenes such as nystatin or amphotericin B, imidazoles such as clotrimazole or miconazole, and oral triazoles such as fluconazole or itraconazole, are equally effective [ 8 ]. Cotrimoxazole (trimethoprim-sulfamethoxazole) was the most frequently prescribed drug, a finding that might be explained by the fact that it is a safe, effective, low-cost combination antibiotic prescribed for the treatment of a wide range of bacterial, parasitic, and fungal infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recent guidelines of the German Society of Gynecology and Obstetrics indicate that the treatment of VVC with the antimycotic agents available on the market is successful in most cases, and that polyenes such as nystatin or amphotericin B, imidazoles such as clotrimazole or miconazole, and oral triazoles such as fluconazole or itraconazole, are equally effective [ 8 ]. Cotrimoxazole (trimethoprim-sulfamethoxazole) was the most frequently prescribed drug, a finding that might be explained by the fact that it is a safe, effective, low-cost combination antibiotic prescribed for the treatment of a wide range of bacterial, parasitic, and fungal infections [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, besides a broad-spectrum activity our findings revealed that cotrimoxazole had a low resistance rate of 13%. Third, increasing evidence from antibiotic prophylaxis with cotrimoxazole in HIV-infected adults and children showed that long-term therapy is safe and inexpensive [35,36,37]. Fourth, there is also strong evidence showing that, in addition to its antimicrobial properties, cotrimoxazole also has immunomodulatory and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported potential risks of abortion and physical deformation of the foetus in the first semester of the pregnancy ( Richardson et al., 2000 ; Czeizel et al., 2001 ; Straub 2016 ). Other studies have reported that the risk of birth defects and malformation of the foetus in pregnant women is low and that the benefit of the medication outweighs its potential health risks ( Ford et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%